English pronunciation difficulties of selected Cebuano speakers in U.P. Kalayaan Residence Hall - Gelbolingo, Juliemie B.; Belarmino, Philip J. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2003)
This study shows the application of Robert Lado's Contrastive Analysis to account for the pronunciation problems of Cebuanos in learning English by showing the contrasting features of Cebuano and English phonemes. Contrastive analysis predicts that the similarities of the characteristics of Cebuano and English will not cause any problems for Cebuano learners. On the other hand, the differences will cause negative transfer which result in errors in pronunciation. For the application of the study, a recording activity is performed by the researcher. The result shows that all the speakers do not have production problems of the English consonants except for the aspirated allophones. Most of the errors are concentrated in the production of vowel sounds. The result shows that the predictions of the contrastive analysis of Cebuano and English phonology which states that due to structural differences, negative transfer will happen in a one-way direction (from native language to target language) cannot exclusively account for all the errors encountered by the speakers.
Thesis (B.A. in English Studies)
Includes bibliographical references and appendices
Keywords: Cebuano language -- Grammar, Comparative -- English; Contrastive linguistics -- Philippines -- Cebu; English language -- Pronunciation; Articulation disorders -- Philippines -- Cebu